2015
DOI: 10.1038/ncomms8790
|View full text |Cite
|
Sign up to set email alerts
|

Transient signal generation in a self-assembled nanosystem fueled by ATP

Abstract: A fundamental difference exists in the way signal generation is dealt with in natural and synthetic systems. While nature uses the transient activation of signalling pathways to regulate all cellular functions, chemists rely on sensory devices that convert the presence of an analyte into a steady output signal. The development of chemical systems that bear a closer analogy to living ones (that is, require energy for functioning, are transient in nature and operate out-of-equilibrium) requires a paradigm shift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
112
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 49 publications
1
112
0
Order By: Relevance
“…A strong decrease of the ATP absorbance maximum at 260 nm showed that a relevant amount of ATP was removed from the solution (Figure S21). Further confirmation was obtained by testing the ATP stability under hydrolytic conditions installed by the presence of potato apyrase, an enzyme that hydrolyses ATP into adenosine 5’‐monophosphate (AMP) and two molecules of orthophosphate P i , . ATP (20 μM) was added to a pre‐equilibrated solution of C 20 TACN ⋅ Zn 2+ disks and DPH (2 μM) in the presence or absence of potato apyrase (1.5 U mL −1 , [CaCl 2 ]=0.25 mM, 37 °C) and the FI intensity was measured as a function of time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A strong decrease of the ATP absorbance maximum at 260 nm showed that a relevant amount of ATP was removed from the solution (Figure S21). Further confirmation was obtained by testing the ATP stability under hydrolytic conditions installed by the presence of potato apyrase, an enzyme that hydrolyses ATP into adenosine 5’‐monophosphate (AMP) and two molecules of orthophosphate P i , . ATP (20 μM) was added to a pre‐equilibrated solution of C 20 TACN ⋅ Zn 2+ disks and DPH (2 μM) in the presence or absence of potato apyrase (1.5 U mL −1 , [CaCl 2 ]=0.25 mM, 37 °C) and the FI intensity was measured as a function of time.…”
Section: Resultsmentioning
confidence: 99%
“…Further confirmation was obtained by testing the ATP stability under hydrolytic conditions installed by the presence of potato apyrase, an enzyme that hydrolyses ATP into adenosine 5'-monophosphate (AMP) and two molecules of orthophosphate P i . [41,48] ATP (20 mM) was added to a pre-equilibrated solution of C 20 TACN · Zn 2 + disks and DPH (2 mM) in the presence or absence of potato apyrase (1.5 U mL À1 , [CaCl 2 ] = 0.25 mM, 37 8C) and the FI intensity was measured as a function of time. Comparison of the two samples showed that, under dissipative conditions, the FI intensity decreased only very slowly over the time course of hours indicating a very high stability of the stacked disks.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 This is also relevant to the fields of enzymeresponsive structures and nanomaterials that respond to ATP signaling. [3][4][5] Indeed, the monitoring of ATP hydrolysis is of fundamental importance to achieve bioinspired ATP-fueled dissipative self-assembled systems, such as micellar or vesicular structures, or supramolecular polymers. 1,[6][7][8][9][10][11] To follow the evolution of ATP hydrolysis in real time, mostly metal ion complexes were exploited, in which the metal ions bind ATP.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,12 The complexation between these compounds (eg, with Zn 2+ or Tb 3+ metal centers) and ATP yielded hybrid helical supramolecular polymers or multivalent self-assembled platforms. 1,2,5,11,12 In contrast, supramolecular systems comprising metal-free organic molecules were barely explored for monitoring ATP hydrolysis, while they offer the advantages of a large conformational diversity (hence a rapid reorganization upon binding), lower toxicity, and the versatility in organic synthesis to limit the aggregation and enhance the detection sensitivity, as compared with metal-based molecules. 13 We have recently shown that an achiral guanidinium derivative functionalized with pyrene moieties (GuaBiPy, Figure 1) is able to self-assemble along oligonucleotides (short DNA) templates in aqueous solutions, through a set of interactions between the guanidinium and the phosphodiester backbone (electrostatic interactions and H-bonds), together with π-π interactions between pyrenes of the molecular guests along the template, as observed through fluorescence signals.…”
Section: Introductionmentioning
confidence: 99%
“…Previously,w eh ave shown that the addition of ATPt o am ultivalent complex of Au NP 1·Zn II ,w hich are gold nanoparticles (d avg = 1.8 AE 0.4 nm) protected with amonolayer of C 9 -alkanethiolates bearing a1 ,4,7-triazacyclononane (TACN)·Zn II complex as head group,a nd fluorogenic probe A resulted in the displacement of A from Au NP 1·Zn II and, consequently,aturn-on of fluorescence ( Figure 1). [17,18] Under dissipative conditions,installed by the presence of ahydrolytic enzyme,A TP was gradually converted into waste products, AMP and 2P i ,with alow affinity for Au NP 1·Zn II .Asaresult, probe A re-associated to Au NP 1·Zn II causing aspontaneous decrease in the fluorescence intensity.Inafollow-up study it was demonstrated that the lifetime of the transient signal could be tuned by exploiting the different resistances of various fuels against hydrolytic cleavage. [19] Yet, the affinity of these fuels for Au NP 1·Zn II was in all cases dominated by strong multivalent electrostatic interactions and no fuel selectivity was observed.…”
mentioning
confidence: 99%